2014
DOI: 10.1016/j.rppnen.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing exercise training in pulmonary rehabilitation: A clinical experience

Abstract: Built around exercise training, pulmonary rehabilitation (PR) is a multidisciplinary, evidence-based, comprehensive approach to working with the patient as a whole and not just the pulmonary component of the disease. Integrated into the individualized treatment, this intervention aims to reduce symptoms, optimize functional status, increase participation in daily life, and reduce health care costs through stabilizing or reversing systemic manifestations of the disease. Although there are many other components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…23 This study found no evidence of significant decrease in left ventricular function at rest in the patients with PAH and left ventricular function at peak exercise was maintained similar to healthy controls before and after AET. The AET regimen used in this study was substantially more intense and prolonged compared to other studies in patients with severe chronic illnesses, [24][25][26] including PAH, [27][28][29][30][31][32] or individuals who are sedentary but otherwise healthy. 33 While significant benefits of participating in AET for people with PAH have been reported previously, 16,17 the current findings suggest that participation in AET appears to be safe and without adverse consequences on left ventricular function.…”
Section: Discussionmentioning
confidence: 99%
“…23 This study found no evidence of significant decrease in left ventricular function at rest in the patients with PAH and left ventricular function at peak exercise was maintained similar to healthy controls before and after AET. The AET regimen used in this study was substantially more intense and prolonged compared to other studies in patients with severe chronic illnesses, [24][25][26] including PAH, [27][28][29][30][31][32] or individuals who are sedentary but otherwise healthy. 33 While significant benefits of participating in AET for people with PAH have been reported previously, 16,17 the current findings suggest that participation in AET appears to be safe and without adverse consequences on left ventricular function.…”
Section: Discussionmentioning
confidence: 99%
“…A reabilitação pulmonar é uma das intervenções mais eficazes no manejo da DPOC [24]. Trata-se de uma terapia não farmacológica, definida como programa de intervenção multidisciplinar que envolve abordagens terapêuticas, suporte emocional, educação e recondicionamento físico, com o objetivo de melhorar e controlar os sintomas, diminuir as complicações da doença [25].…”
Section: Tratamento Incluindo Reabilitação Pulmonar E Condicionamento Físicounclassified
“…Patients with COPD and Asthma also show greater exercise intolerance, frequent bouts of dyspnea, more significant participation restrictions, and lower quality of life [36]. Aerobic exercises combined with bronchodilators can remove the struggle with most of the patients initiating the exercise program.…”
Section: Effect Of Aerobic Exercisementioning
confidence: 99%
“…Aerobic exercises combined with bronchodilators can remove the struggle with most of the patients initiating the exercise program. The current guidelines for PR are programmed to two to five times a week for 6-12 weeks [23,36]. It's advisable to incorporate a short-acting b2-agonist before 15 min of starting the exercise to prevent exercise-induced airway hyper-responsiveness [23].…”
Section: Effect Of Aerobic Exercisementioning
confidence: 99%